Tahap Penerimaan Dan Aplikasi Teknologi Maklumat Di Kalangan Guru Sekolah Menengah - Hong, Siok Lin (2001)

(untitled)
In the era of information technology, a paradigm shift has occurred in the approach of learning and teaching in classroom. The changing role of teachers in classroom that equipped with advanced computer technology can have serious influence to various aspects. The purpose of this study is to identify the level of acceptance and application of computer technology among the secondary school teachers. The study is aimed specifically to determine the level of knowledge, interest, skill, character and self-effectiveness of teachers towards the adoption of computer technology. This also includes the objective of the utilization of computer technology, the relationship of computer application according to various factors (knowledge, skill, interest and self-effectiveness) with teachers' attitude and the different of factors of age, sex, field of specialization, teaching experience, academic qualification and frequency of using computer with teachers' approach in the application of computer. The outcome of study showed that teachers have a fair scoring of knowledge, interest, skill, character and self-effectiveness level. There is a significant relationship between knowledge factors, skill and self-effectiveness with the attitude of teachers. There is, however, less significant relationship between interest factors with the attitude of teacher in the application of computer technology. In addition, there is significant difference of frequency, age, and field of specialization with the attitude towards the computer technology. The result of study also shows that there is a significant difference between the men and the women where the t-test analysis shows that women respondent group tends to demonstrate a more positive approach as compared to its opposite sex respondent group.